Origins of the Cold War an international history - Leffler, Melvyn P. 1945-; Painter, David S. (Rewriting histories., 2005)
This second edition brings the collection up to date, including the newest research from the Communist side of the Cold War and the most recent debates on culture, race and intelligence.